Iuiga: Defining an omni-channel strategy - TULI, Kapil R. (Institutional Knowledge at Singapore Management University, 2019)
Iuiga, a lifestyle retailer, has a curated range of high quality products at transparent, affordable prices, effectively leveraging the original design manufacturers’ model and an online retail platform.